Performance, Egg Quality, Bone Health, and Immunity Assessments of Lohmann Laying Hens Supplemented with Vitamin D3 in the Diet - Yusuf, G. M.; Sumiati; Mutia, R.; Wardani, W. W.; Akbar, I.; Putri, N. D. S. (Tropical Animal Science Journal, 2023)
Bone health in laying hens is associated with production performance and physical egg quality. This study aimed to evaluate the effects of a diet supplemented with Nutricell Eggstra (vitamin D3 enriched with canthaxanthin) on the production performance, egg quality, bone mineral, and immunity of laying hens. Herein, 150 Lohmann laying hens were divided into three treatments with five replicates. The treatment diets were: T1= diet without Nutricell Eggstra supplementation (control), T2= diet supplemented with 1.00 kg/ton Nutricell Eggstra, and T3= diet supplemented with 1.50 kg/ton Nutricell Eggstra. Compared to the control diet, supplementation of Nutricell Eggstra at doses of 1.00 kg/ton and 1.50 kg/ton significantly increased (p